Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery including same
By using the cathode active material composed of the aggregated secondary particles and single particles and performing boron coating treatment on its surface, the problem of structure vulnerability to the cathode active material of lithium-ion batteries during repeated charging and discharging is solved, and higher charge and discharge efficiency and life characteristics are achieved.
Patent Information
- Application Number
- JP2023119255
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-14
- Filing Date
- 2023-07-21
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2043-07-21
AI Technical Summary
The structure of the positive electrode active material of existing lithium-ion batteries is easily damaged during repeated charging and discharge, resulting in a shortened battery life and poor capacitance performance.
A positive electrode active material consisting of secondary particles and single particles formed by aggregation of multiple primary particles is used and boron coating is treated on its surface to enhance the stability and surface roughness of the material.
The charge and discharge efficiency and life characteristics of the positive electrode active material are improved, and the safety and energy density of the battery are enhanced.
Smart Images

Figure 0007669428000005 
Figure 0007669428000006 
Figure 0007669428000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same. [Background technology]
[0002] Lithium secondary batteries, which have high energy density yet are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been investigated. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, such positive electrode active materials have problems in that the structure collapses or cracks occur due to repeated charging and discharging, thereby reducing the long-term life of the lithium secondary battery, and the resistance increases, making it impossible to exhibit satisfactory capacity characteristics. Therefore, there is a need to develop a new positive electrode active material that can achieve high capacity and high energy density while ensuring long-term life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0004] By mixing a secondary particle type positive electrode active material with a single particle type positive electrode active material, the efficiency of the single particle positive electrode active material is increased, and the performance of the lithium secondary battery containing this, such as the initial charge / discharge efficiency and life characteristics, as well as the safety of the battery, are improved. [Means for solving the problem]
[0005] In one embodiment, there is provided a positive electrode active material for a lithium secondary battery, comprising: a first positive electrode active material comprising a lithium-nickel-based composite oxide and including secondary particles formed by agglomeration of a plurality of primary particles and a boron coating portion located on a surface of the secondary particles; and a second positive electrode active material comprising a lithium-nickel-based composite oxide and including a single particle and a boron coating portion located on a surface of the single particle, the second positive electrode active material having an uneven surface with unevenness and a flat surface without unevenness.
[0006] In another embodiment, there is provided a method for producing a positive electrode active material for a lithium secondary battery, comprising: mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide; mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide; and mixing the first nickel-based oxide, the second nickel-based oxide, and a boron raw material and performing a third heat treatment.
[0007] In yet another embodiment, a lithium secondary battery is provided that includes a positive electrode containing the positive electrode active material, a negative electrode, and an electrolyte. Effect of the Invention
[0008] The efficiency of the positive electrode active material in the form of single particles is increased, and the performance of the lithium secondary battery, such as the initial charge / discharge efficiency and life characteristics, as well as the safety of the battery, are improved. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. [Diagram 2] 2 is a scanning electron microscope (SEM) photograph of the surface of a first positive electrode active material of Example 1. [Diagram 3] 4 is a SEM photograph of a second positive electrode active material of Example 1. [Figure 4] 4 is a SEM photograph of a second positive electrode active material of Example 1. [Diagram 5] 1 is a SEM photograph of the surface of a first positive electrode active material of Comparative Example 1. [Figure 6]1 is a SEM photograph of a second positive electrode active material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Although the present invention may be embodied in many different forms, it is not intended to be limited to the embodiments set forth herein, but rather to be limited to the specific embodiments set forth herein.
[0011] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0012] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0013] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, and do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0014] In the drawings, the thickness of layers and regions is exaggerated to clearly show them, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, or plate is said to be "on" another part, this includes not only the case where the part is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" the other part, it means that there is no other part between them.
[0015] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.
[0016] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope or a scanning electron microscope. In another method, the average particle size can be calculated by measuring the number of particles in each particle size range using a dynamic light scattering method and performing data analysis. Unless otherwise defined, the average particle size can mean the diameter of the particles whose cumulative volume is 50% by volume in the particle size distribution (D50).
[0017] As used herein, "or" is not to be construed in the exclusive sense, e.g., "A or B" is to be construed as including A, B, A+B, etc.
[0018] The term "metal" is understood to include general metals, transition metals, and metalloids (semimetals).
[0019] positive electrode active material In one embodiment, a positive electrode active material for a lithium secondary battery is provided, the positive electrode active material comprising a first positive electrode active material, the first positive electrode active material being in the form of secondary particles formed by agglomeration of a plurality of primary particles, the first positive electrode active material being in the form of a single particle, the second positive electrode active material being in the form of a single particle, the second positive electrode active material having an uneven surface with unevenness and a flat surface without unevenness. Such a positive electrode active material has a high pellet density and can achieve a high capacity, and therefore has a high energy density, a high charge / discharge efficiency, and excellent life characteristics at room temperature and high temperature.
[0020] First positive electrode active material The first positive electrode active material is in the form of polycrystal and in the form of secondary particles in which at least two or more primary particles are aggregated. The first positive electrode active material includes a boron coating portion located on the surface of the secondary particle. The boron coating portion may be located on the entire surface or at least a portion of the surface of the secondary particle, and may be present in the form of a continuous film or a silicide film on the surface of the secondary particle. By including the boron coating portion, the first positive electrode active material can effectively prevent the collapse of the structure due to repeated charging and discharging, thereby improving the room temperature and high temperature life characteristics.
[0021] The boron coating portion includes a boron-containing compound, which may include, for example, boron oxide, lithium borate, or a combination thereof, such as B2O2, B2O3, B4O3, B4O5, LiBO2, Li3BO, 12 , Li6B4O9, Li3B 11 O 18 , Li2B4O7, Li3BO3, or combinations thereof.
[0022] The content of boron in the first positive electrode active material relative to the total content of elements excluding lithium and oxygen may be 0.01 mol% to 3 mol%, for example, 0.01 mol% to 2 mol%, 0.01 mol% to 1 mol%, or 0.05 mol% to 0.5 mol%. The content of boron in the first positive electrode active material relative to the total content of elements excluding lithium and oxygen may be 0.01 wt% to 3 wt%, for example, 0.01 wt% to 2 wt%, 0.01 wt% to 1 wt%, or 0.01 wt% to 0.5 wt%. The content of boron may be measured, for example, by ICP (Inductively Coupled Plasma) emission spectroscopy. When boron is coated at such a content, it does not act as a resistor, the battery capacity does not decrease, and lithium ions are more easily diffused into the positive electrode active material, improving the initial charge / discharge efficiency, and problems caused by repeated charge / discharge are suppressed, thereby improving the long life characteristics of the battery.
[0023] The thickness of the boron coating portion of the first positive electrode active material varies depending on the baking temperature during coating, and may be, for example, 1 nm to 2 μm, 1 nm to 1.5 μm, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, a lithium secondary battery including the first positive electrode active material may exhibit excellent room temperature and high temperature life characteristics. The thickness of the boron coating portion may be measured by TOF-SIMS, XPS, or EDS, for example, by TEM-EDS line profile.
[0024] The average particle size of the first positive electrode active material, that is, the average particle size of the secondary particles, may be 5 μm to 25 μm. For example, it may be 7 μm to 25 μm, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The average particle size of the secondary particles of the first positive electrode active material may be larger than the average particle size of the second positive electrode active material in the form of a single particle, which will be described later. The positive electrode active material according to an embodiment may be in a form in which the first positive electrode active material, which is polycrystalline and large particles, and the second positive electrode active material, which is single particles and small particles, are mixed together, and therefore the mixture density can be improved, and high capacity and high energy density can be achieved.
[0025] The first positive electrode active material is a nickel-based positive electrode active material and includes a lithium nickel-based composite oxide (or a first nickel-based oxide). The content of nickel in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of metals excluding lithium, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. For example, the content of nickel in the lithium nickel-based composite oxide may be higher than the content of each of other metals such as cobalt, manganese, and aluminum. When the content of nickel satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving high capacity.
[0026] Specifically, the first positive electrode active material may include a lithium nickel-based composite oxide represented by the following Chemical Formula 1.
[0027] [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1
[0028] In the formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, 0≦y1≦0.7, 0≦z1≦0.7, 0.9≦x1+y1+z1≦1.1, and 0≦b1≦0.1; M 1 and M. 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
[0029] In the above Chemical Formula 1, 0.4≦x1≦1, 0≦y1≦0.6, and 0≦z1≦0.6 may be satisfied; 0.5≦x1≦1, 0≦y1≦0.5, and 0≦z1≦0.5 may be satisfied; 0.6≦x1≦1, 0≦y1≦0.4, and 0≦z1≦0.4 may be satisfied; 0.7≦x1≦1, 0≦y1≦0.3, and 0≦z1≦0.3 may be satisfied; 0.8≦x1≦1, 0≦y1≦0.2, and 0≦z1≦0.2 may be satisfied; or 0.9≦x1≦1, 0≦y1≦0.1, and 0≦z1≦0.1 may be satisfied.
[0030] The first positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following chemical formula 2.
[0031] [Chemical formula 2] Li a2 Ni x2 Co y2 M 3 z2 O2-b2 X b2
[0032] In the above formula 2, 0.9≦a2≦1.8, 0.3≦x2<1, 0 <y2≦0.7、0≦z2≦0.7、0.9≦x2+y2+z2≦1.1、および0≦b2≦0.1であり、M 3 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
[0033] In the formula 2, 0.3≦x2≦0.99 and 0.01≦y2≦0.7 and 0.01≦z2≦0.7 may be satisfied; 0.4≦x2≦0.99 and 0.01≦y2≦0.6 and 0.01≦z2≦0.6 may be satisfied; 0.5≦x2≦0.99 and 0.01≦y2≦0.5 and 0.01≦z2≦0.5 may be satisfied; or 0.6≦x2≦0.99 and 0.01≦y2≦0.7 and 0.01≦z2≦0.7 may be satisfied; 2≦0.4 and 0.01≦z2≦0.4, or 0.7≦x2≦0.99 and 0.01≦y2≦0.3 and 0.01≦z2≦0.3, or 0.8≦x2≦0.99 and 0.01≦y2≦0.2 and 0.01≦z2≦0.2, or 0.9≦x2≦0.99 and 0.01≦y2≦0.1 and 0.01≦z2≦0.1.
[0034] The first positive electrode active material may include, for example, a compound represented by Formula 3 below.
[0035] [Chemical formula 3] Li a3 Ni x3 Co y3 M 4 z3 M 5 w3 O 2-b3 X b3
[0036] In the formula 3, 0.9≦a3≦1.8, 0.3≦x3≦0.98, 0.01≦y3≦0.69, 0.01≦z3≦0.69, 0≦w3≦0.69, 0.9≦x3+y3+z3+w3≦1.1, and 0≦b3≦0.1; 4 is one or more elements selected from the group consisting of Al and Mn, 5 is one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
[0037] In the formula 3, 0.4≦x3≦0.98, 0.01≦y3≦0.59, and 0.01≦z3≦0.59 and 0≦w3≦0.59 may be satisfied, 0.5≦x3≦0.98, 0.01≦y3≦0.49, and 0.01≦z3≦0.49 and 0≦w3≦0.49 may be satisfied, or 0.6≦x3≦0.98, 0.01≦y3≦0.39, and 0.01≦z3≦0.39 and 0≦w3≦0.39 may be satisfied. or 0.7≦x3≦0.98, 0.01≦y3≦0.29, and 0.01≦z3≦0.29 and 0≦w3≦0.29, or 0.8≦x3≦0.98, 0.01≦y3≦0.19, and 0.01≦z3≦0.19 and 0≦w3≦0.19, or 0.9≦x3≦0.98, 0.01≦y3≦0.09, and 0.01≦z3≦0.09 and 0≦w3≦0.09.
[0038] Meanwhile, the maximum roughness of the surface of the first positive electrode active material may be, for example, 3 nm to 80 nm, 5 nm to 70 nm, or 10 nm to 65 nm, the average roughness may be 0.2 nm to 5 nm, or 0.2 nm to 4 nm, and the root-mean-square roughness may be 0.5 nm to 10 nm, 0.5 nm to 9 nm, 0.5 nm to 8 nm, or 0.7 nm to 7 nm. Details of the meanings and measuring methods of the maximum roughness, average roughness, and root-mean-square roughness will be described later in the section on the second positive electrode active material.
[0039] Second positive electrode active material The second positive electrode active material is in the form of a single particle (one body), which means that the second positive electrode active material is present alone without a grain boundary within the particle and is composed of one particle, and may mean a monolith structure or a single body structure or non-aggregated particles in which the particles are present in an independent phase that does not aggregate with each other in terms of morphology, and may be a single crystal, for example. The positive electrode active material according to an embodiment may exhibit improved life characteristics while realizing high capacity and high energy density by including such a second positive electrode active material.
[0040] The shape of the second positive electrode active material is not particularly limited, and may have various shapes such as a polyhedron, a sphere, an ellipse, a plate shape, a rod shape, an irregular shape, etc. The second positive electrode active material in the form of a single particle according to an embodiment may have a polyhedron structure having two or more faces.
[0041] According to an embodiment, the second positive electrode active material includes a boron coating portion located on a surface of a single particle. The boron coating portion includes a boron-containing compound, which may include, for example, boron oxide, lithium borate, or a combination thereof, for example, B2O2, B2O3, B4O3, B4O5, LiBO2, Li3BO, 12 , Li6B4O9, Li3B 11 O 18 , Li2B4O7, Li3BO3, or a combination thereof. The second positive electrode active material is coated with a boron-containing compound, which effectively prevents the structure from collapsing due to repeated charging and discharging, thereby improving the room temperature and high temperature life characteristics.
[0042] In a method for producing a positive electrode active material according to an embodiment described below, boron coating is not performed separately on the first positive electrode active material and the second positive electrode active material, but the first nickel-based oxide, the second nickel-based oxide, and the boron raw material are mixed together and then the third heat treatment is performed to perform simultaneous coating (or simultaneous firing). According to this, it is confirmed that the boron-containing compound is effectively coated only on a part of the crystal surface of the second positive electrode active material in the form of a single particle, and unevenness occurs in this part. For this reason, one single particle of the second positive electrode active material includes both an uneven surface having a specific unevenness and an uneven surface having a specific unevenness and a flat and uniform flat surface. This is understood to be because the boron-containing compound is effectively coated only on the crystal surface where lithium ions are likely to enter and exit, and unevenness occurs. In such a second positive electrode active material, the surface roughness of a specific surface is increased, and the specific surface area of the second positive electrode active material and the entire positive electrode active material including the same is increased. A lithium secondary battery including such a positive electrode active material can improve initial discharge capacity, charge / discharge efficiency, and life characteristics.
[0043] The unevenness of the uneven surface is not a layered or stepped structure formed during the formation of the lithium nickel composite oxide in the form of a single particle, but is formed while the boron-containing compound is coated, that is, formed while the boron-containing compound is attached to the surface of the single particle, and may be in the form of water droplets, wrinkles, or columns arranged side by side. It can also be expressed as a shape in which the boron-containing compound covers part of the surface of the single particle in an uneven form. This form is distinguished from the existing Irish-type coating.
[0044] A single particle of the second positive electrode active material may include a concave-convex surface having a high surface roughness and a flat surface having a low surface roughness. That is, in the second positive electrode active material, the concave-convex surface has a high surface roughness. The surface roughness may be measured using a surface roughness measuring device, for example, an optical profiler, using a photograph of an object taken by an atomic force microscopy (AFM) or the like.
[0045] The maximum surface roughness (R max v) maximum roughness depth can mean the vertical distance between the highest peak and the lowest valley of a roughness profile. a Average roughness, also called center line average roughness, can mean the arithmetic mean of the absolute values of the ordinates of the roughness profile. q Root mean square roughness (rms) may refer to the root mean square (rms) of the vertical values in the roughness profile. For such surface roughness, reference may be made to the parameter definition and measurement method defined in KS B 0601 or ISO 4287 / 1.
[0046] The uneven surface of the second positive electrode active material has a maximum roughness (R max ; peak to peak height) may be 15 nm or more, for example, 16 nm or more, and may be 15 nm to 100 nm, 15 nm to 80 nm, 15 nm to 60 nm, or 15 nm to 40 nm. In this case, the positive electrode active material for a lithium secondary battery containing the second positive electrode active material exhibits high energy density and high capacity, and can realize excellent charge / discharge efficiency and life characteristics.
[0047] The uneven surface of the second positive electrode active material has an average roughness (R a ; average roughness) may be 1.2 nm or more, for example, 1.3 nm or more, and may be 1.2 nm to 10 nm, 1.2 nm to 8.0 nm, 1.2 nm to 6.0 nm, 1.2 nm to 5.0 nm, or 1.2 nm to 3.0 nm. In this case, the positive electrode active material for lithium secondary batteries containing the second positive electrode active material exhibits high energy density and high capacity, and can realize excellent charge / discharge efficiency and life characteristics.
[0048] The uneven surface of the second positive electrode active material has a root mean square roughness (R q; root mean square roughness) may be 1.5 nm or more, for example, 1.6 nm or more, and may be 1.5 nm to 10 nm, 1.5 nm to 8 nm, 1.5 nm to 6 nm, 1.5 nm to 5 nm, or 1.5 nm to 3 nm. In this case, the positive electrode active material for a lithium secondary battery containing the second positive electrode active material exhibits high energy density and high capacity, and can realize excellent charge / discharge efficiency and life characteristics.
[0049] On the other hand, the flat surface of the second positive electrode active material may exhibit a lower surface roughness than the uneven surface. For example, the flat surface of the second positive electrode active material may exhibit a maximum roughness (R max The flat surface of the second positive electrode active material may have an average roughness (R a The flat surface of the second positive electrode active material may have a root mean square roughness (R q ) may be less than 1.5 nm, for example, 0.1 nm to 1.4 nm, or 0.5 nm to 1.4 nm.
[0050] The second positive electrode active material, which has both uneven and flat surfaces in this way, can achieve high capacity and high energy density while having a stable structure that does not collapse during charging and discharging of the battery, and can exhibit excellent life characteristics.
[0051] The content of boron in the second positive electrode active material relative to the total content of elements excluding lithium and oxygen may be 0.01 mol% to 3 mol%, for example, 0.01 mol% to 2 mol%, 0.01 mol% to 1 mol%, or 0.05 mol% to 0.5 mol%. The content of boron in the second positive electrode active material relative to the total content of elements excluding lithium and oxygen may be 0.01 wt% to 3 wt%, for example, 0.01 wt% to 2 wt%, 0.01 wt% to 1 wt%, or 0.01 wt% to 0.5 wt%. The content of boron may be measured, for example, by ICP (Inductively Coupled Plasma) emission spectroscopy. When boron is coated at such a content, it does not act as a resistor, the battery capacity does not decrease, and the performance of the second positive electrode active material in the form of a single particle can be maximized.
[0052] The ratio of the uneven surface to the total surface area of the second positive electrode active material may be about 40% to 80%, for example, 45% to 80%, or 50% to 75%. The ratio of the flat surface to the total surface area of the second positive electrode active material may be about 20% to 60%, for example, 20% to 55%, or 25% to 50%. By including the uneven surface and the flat surface at such a ratio, the second positive electrode active material can exhibit high capacity and long life characteristics.
[0053] The thickness of the boron coating portion of the second positive electrode active material may be about 1 nm to 2 μm, for example, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, a lithium secondary battery including the second positive electrode active material may exhibit excellent normal temperature and high temperature life characteristics. The thickness of the boron coating portion may be measured by TOF-SIMS, XPS, or EDS, for example, by TEM-EDS line profile.
[0054] The average particle size of the second positive electrode active material, i.e., the average particle size of a single particle, may be 0.05 μm to 10 μm, for example, 0.1 μm to 8 μm, 0.1 μm to 7 μm, 0.1 μm to 6 μm, 0.1 μm to 10 μm, 0.5 μm to 9 μm, 1 μm to 8 μm, specifically 1 μm to 5 μm. The particle size of the second positive electrode active material may be smaller than that of the first positive electrode active material, thereby further increasing the density of the positive electrode active material.
[0055] The BET specific surface area of the entire positive electrode active material including the first positive electrode active material and the second positive electrode active material is 0.2 m 2 / g~0.6m 2 / g, for example 0.3m 2 / g~approx.0.5m 2 / g, 0.3m 2 / g~approx.0.4m 2 / g. In this case, the positive electrode active material can achieve excellent charge / discharge efficiency and life characteristics. The BET specific surface area may be measured by a nitrogen gas adsorption method using, for example, a specific surface area measuring device HM model-1208 manufactured by MOUNTECH. Specifically, about 0.3 g of a positive electrode active material sample is heated in a nitrogen atmosphere at 300°C in a pretreatment device for 1 hour, and then pretreated for an additional 15 minutes at 300°C in a specific surface area measuring device, cooled to the temperature of liquid nitrogen, and saturated adsorbed with a gas containing 30% nitrogen and 70% He. Thereafter, the amount of gas desorbed by heating to room temperature is measured, and the specific surface area can be calculated from the obtained results by a conventional BET method.
[0056] The second positive electrode active material is a nickel-based active material and includes a lithium nickel-based composite oxide (or a second nickel-based oxide). The content of nickel in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of metals excluding lithium, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. For example, the content of nickel in the lithium nickel-based composite oxide may be higher than the content of each of other metals such as cobalt, manganese, and aluminum. When the content of nickel satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving high capacity.
[0057] The second positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following formula 11.
[0058] [Chemical formula 11] Li a11 Ni x11 M 11 y11 M 12 z11 O 2-b11 X b11
[0059] In the formula 11, 0.9≦a11≦1.8, 0.3≦x11≦1, 0≦y11≦0.7, 0≦z11≦0.7, 0.9≦x11+y11+z11≦1.1, and 0≦b11≦0.1; M 11 and M. 12 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
[0060] In the formula 11, 0.4≦x11≦1 and 0≦y11≦0.6 and 0≦z11≦0.6 may be satisfied, 0.5≦x11≦1 and 0≦y11≦0.5 and 0≦z11≦0.5 may be satisfied, or 0.6≦x11≦1 and 0≦y11≦0.4 and 0≦z11≦0.4 may be satisfied, or 0.7≦x11≦1 and 0≦y11≦0.3 and 0≦z11≦0.3 may be satisfied, or 0.8≦x11≦1 and 0≦y11≦0.2 and 0≦z11≦0.2 may be satisfied, or 0.9≦x11≦1 and 0≦y11≦0.1 and 0≦z11≦0.1 may be satisfied.
[0061] The second positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following Chemical Formula 12.
[0062] [Chemical formula 12] Li a12 Ni x12 Co y12 M 13 z12 O 2-b12 X b12
[0063] In the formula 12, 0.9≦a12≦1.8, 0.3≦x12<1, 0 <y12≦0.7、0≦z12≦0.7、0.9≦x12+y12+z12≦1.1、および0≦b12≦0.1であり、M 13 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
[0064] In the formula 12, 0.3≦x12≦0.99 and 0.01≦y12≦0.7 and 0≦z12≦0.7 may be satisfied; 0.4≦x12≦0.99 and 0.01≦y12≦0.6 and 0≦z12≦0.6 may be satisfied; 0.5≦x12≦0.99 and 0.01≦y12≦0.5 and 0≦z12≦0.5 may be satisfied; or 0.6≦x12≦0.99 and 0.01≦y12≦0.5 and 0≦z12≦0.5 may be satisfied. ≦y12≦0.4 and 0≦z12≦0.4, or 0.7≦x12≦0.99 and 0.01≦y12≦0.3 and 0≦z12≦0.3, or 0.8≦x12≦0.99 and 0.01≦y12≦0.2 and 0≦z12≦0.2, or 0.9≦x12≦0.99 and 0.01≦y12≦0.1 and 0≦z12≦0.1.
[0065] The second positive electrode active material may include, for example, a lithium nickel cobalt composite oxide represented by the following Chemical Formula 13.
[0066] [Chemical formula 13] Li a13 Ni x13 Co y13 M 14 z13 M 15 w13 O 2-b13 X b13
[0067] In the formula 13, 0.9≦a13≦1.8, 0.3≦x13≦0.98, 0.01≦y13≦0.69, 0.01≦z13≦0.69, 0≦w13≦0.69, 0.9≦x13+y13+z13+w13≦1.1, and 0≦b13≦0.1; 14 is one or more elements selected from the group consisting of Al and Mn, 15 is one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, and Zr.
[0068] In the formula 13, 0.4≦x13≦0.98, 0.01≦y13≦0.59, and 0.01≦z13≦0.59 and 0≦w13≦0.59 may be satisfied, 0.5≦x13≦0.98, 0.01≦y13≦0.49, and 0.01≦z13≦0.49 and 0≦w13≦0.49 may be satisfied, or 0.6≦x13≦0.98, 0.01≦y13≦0.39, and 0.01≦z13≦0.39 and 0≦w13≦0.39 may be satisfied. or 0.7≦x13≦0.98, 0.01≦y13≦0.29, and 0.01≦z13≦0.29 and 0≦w13≦0.29, or 0.8≦x13≦0.98, 0.01≦y13≦0.19, and 0.01≦z13≦0.19 and 0≦w13≦0.19, or 0.9≦x13≦0.98, 0.01≦y13≦0.09, and 0.01≦z13≦0.09 and 0≦w13≦0.09.
[0069] In the positive electrode active material according to an embodiment, the first positive electrode active material may be included in an amount of 50% by weight to 90% by weight, and the second positive electrode active material may be included in an amount of 10% by weight to 50% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material. The first positive electrode active material may be included in an amount of, for example, 60% by weight to 90% by weight, or 70% by weight to 90% by weight, and the second positive electrode active material may be included in an amount of 10% by weight to 40% by weight, or 10% by weight to 30% by weight. When the content ratio of the first positive electrode active material to the second positive electrode active material is as described above, the positive electrode active material including the first positive electrode active material and the second positive electrode active material may achieve high capacity, have improved mixture density, and exhibit high energy density.
[0070] The boron content of the total element content excluding lithium and oxygen in the entire positive electrode active material including the first positive electrode active material and the second positive electrode active material may be 0.01 mol% to 3 mol%, for example, 0.01 mol% to 2 mol%, 0.01 mol% to 1 mol%, or 0.05 mol% to 0.5 mol%. The boron content of the total element content excluding lithium and oxygen in the entire positive electrode active material may be 0.01 wt% to 3 wt%, for example, 0.01 wt% to 2 wt%, 0.01 wt% to 1 wt%, or 0.01 wt% to 0.5 wt%. The boron content may be measured, for example, by ICP (Inductively Coupled Plasma) emission spectroscopy. When boron is coated at such a content, it does not act as a resistor, the battery capacity does not decrease, and the capacity characteristics and life characteristics can be improved at the same time by maximizing the performance of each of the first positive electrode active material and the second positive electrode active material.
[0071] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material for a lithium secondary battery is provided, the method including mixing a first nickel-based hydroxide and a lithium source and performing a first heat treatment to prepare a first nickel-based oxide, mixing a second nickel-based hydroxide and a lithium source and performing a second heat treatment to prepare a second nickel-based oxide, and mixing the first nickel-based oxide, the second nickel-based oxide, and a boron source and performing a third heat treatment to obtain a final positive electrode active material including the first positive electrode active material and the second positive electrode active material.
[0072] Here, the first nickel-based oxide and the first positive electrode active material are in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the second nickel-based oxide and the second positive electrode active material are in the form of single particles. The first positive electrode active material is a material in which a boron-containing compound is coated on the surface of the first nickel-based oxide, and the second positive electrode active material is a material in which a boron-containing compound is coated on the surface of the second nickel-based oxide.
[0073] In one embodiment, the first and second positive electrode active materials are not individually coated with boron, but the first nickel-based oxide and the second nickel-based oxide are mixed and simultaneously coated with boron. In this way, the second positive electrode active material in the form of a single particle coated with a boron-containing compound has both an uneven surface having an uneven shape and a flat surface having a uniform shape, and therefore has high surface roughness and specific surface area. A positive electrode active material for a lithium secondary battery including such a second positive electrode active material exhibits a high specific surface area and can achieve excellent capacity characteristics and life characteristics.
[0074] The first nickel-based hydroxide and the second nickel-based hydroxide are precursors of a positive electrode active material, and each may be independently a nickel hydroxide, or a nickel-based composite hydroxide containing elements other than nickel, a nickel-metal composite hydroxide containing metals other than nickel, or a nickel-transition metal composite hydroxide containing transition metals other than nickel.
[0075] For example, the first nickel hydroxide and the second nickel hydroxide may each independently be represented by the following Formula 21:
[0076] [Chemical formula 21] Ni x21 M 21 y21 M 22 z21 (OH)2
[0077] In the formula 21, 0.3≦x21≦1, 0≦y21≦0.7, 0≦z21≦0.7, and 0.9≦x21+y21+z21≦1.1; M 21 and M. 22 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0078] The particle size of the first nickel hydroxide may be 10 μm to 30 μm, for example, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The particle size of the second nickel hydroxide may be 1 μm to 9 μm, for example, 2 μm to 9 μm, 2 μm to 8 μm, or 3 μm to 7 μm.
[0079] The lithium source can be, for example, Li2CO3, LiOH, hydrates thereof, or a combination thereof as a lithium source for the positive electrode active material.
[0080] When the first nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0081] The first heat treatment may be performed in an oxidizing gas atmosphere, for example, an oxygen atmosphere or an air atmosphere, and may be performed at 600°C to 900°C or 600°C to 800°C, for example, for 5 to 20 hours or 5 to 15 hours. The first nickel-based oxide obtained through the first heat treatment may be referred to as a first lithium-nickel-based oxide.
[0082] When the second nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0083] The second heat treatment may also be performed in an oxidizing gas atmosphere, for example, an oxygen atmosphere or an air atmosphere, and may be performed at, for example, 800°C to 1100°C or 900°C to 1000°C, for example, 5 to 20 hours or 5 to 15 hours. The second nickel-based oxide obtained through the second heat treatment may also be referred to as a second lithium-nickel-based oxide.
[0084] The second nickel-based oxide has a single particle form, and the single particle form can be obtained by adjusting conditions such as the temperature and time of the second heat treatment, and the single particle form can also be obtained through various conditions when synthesizing the second nickel-based hydroxide by a co-precipitation method.
[0085] The method for manufacturing a positive electrode active material for a lithium secondary battery may further include mixing the second nickel-based hydroxide and a lithium raw material, performing a second heat treatment, and then pulverizing the resultant material, thereby obtaining a second nickel-based oxide in a single particle form. The pulverization may be performed using various pulverizing devices such as a jet mill. Here, pulverizing the resultant material is a process for obtaining an active material in a single particle form, and is different from general crushing of an active material.
[0086] In the process of mixing the first nickel-based oxide and the second nickel-based oxide, the weight ratio of the first nickel-based oxide to the second nickel-based oxide may be 9:1 to 5:5, for example, 9:1 to 6:4, or 8:2 to 7:3. When the mixing ratio of the first nickel-based oxide to the second nickel-based oxide satisfies the above-mentioned range, the manufactured positive electrode active material may exhibit high capacity, high energy density, and high plate density.
[0087] Next, the first nickel-based oxide, the second nickel-based oxide, and the boron source are mixed and subjected to a third heat treatment to perform boron coating. Boron coating can be performed in a dry or wet manner. For example, dry coating can be performed by mixing the first nickel-based oxide, the second nickel-based oxide, and the boron source without a solvent and then performing the third heat treatment. Alternatively, the first nickel-based oxide and the second nickel-based oxide can be added to a solvent such as distilled water, washed while being mixed, and the boron source can be dripped on to perform wet coating and then perform the third heat treatment.
[0088] The boron source is a compound containing boron, such as H3BO3, HBO2, B2O3, C6H5B(OH)2, (C6H5O)3B, [CH3(CH2)3O]3B, (C3H7O)3B, C3H9B3O6, C 13 H 19 BO3, or a combination of these.
[0089] The boron raw material may be mixed so that the boron raw material contains 0.01 to 3 molar parts, or 0.01 to 2 molar parts, or 0.05 to 1.5 molar parts, or 0.1 to 1 molar parts, when the total content of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide is 100 molar parts. When the content of the boron raw material satisfies the above range, boron does not act as a resistor in the positive electrode active material and can play a role in improving the performance of the lithium secondary battery, thereby improving the capacity and life characteristics. If the content of the boron raw material is excessive, boron may act as a resistor in the positive electrode active material, reducing the capacity and life of the battery.
[0090] In one embodiment, when the first nickel-based oxide, the second nickel-based oxide, and the boron source are mixed, a lithium source may be mixed together. The lithium source may be lithium hydroxide, lithium carbonate, or a hydrate thereof. In this case, the amount of the lithium source may be 0.1 to 10 molar parts, 0.5 to 8 molar parts, or 1 to 6 molar parts, based on 100 molar parts of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide as a whole. When the lithium source is added together and the third heat treatment is performed, a stable boron coating part can be effectively formed on the surface of the nickel-based oxide, which is advantageous in obtaining the shape of the second positive electrode active material according to one embodiment.
[0091] The third heat treatment may be performed in an oxidizing gas atmosphere such as oxygen or air, for example, at 650° C. to 900° C. or 650° C. to 800° C. The third heat treatment time varies depending on the heat treatment temperature, but is performed for example, 5 to 30 hours or 10 to 24 hours.
[0092] Then, the heat treatment is terminated and the mixture is cooled at room temperature to manufacture the cathode active material for a lithium secondary battery according to the embodiment described above. The manufactured cathode active material is a mixture of a first cathode active material including secondary particles formed by agglomeration of primary particles and a second cathode active material in the form of single particles, each of which is coated with a boron-containing compound, and the second cathode active material includes both an uneven surface and a flat surface.
[0093] positive electrode The positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer includes a positive electrode active material, and may further include a binder and / or a conductive material.
[0094] The binder serves to favorably adhere the positive electrode active material particles to each other and to favorably adhere the positive electrode active material to a current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0095] The content of the binder in the positive electrode active material layer may be about 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
[0096] The conductive material is used to impart conductivity to the electrodes, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed therewith can be used. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers containing copper, nickel, aluminum, silver, and the like; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures thereof.
[0097] The content of the conductive material in the positive electrode active material layer may be 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
[0098] The positive electrode current collector may be, but is not limited to, an aluminum foil.
[0099] negative electrode The negative electrode for a lithium secondary battery includes a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder and / or a conductive material.
[0100] The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0101] The material capable of reversibly inserting / extracting lithium ions may be a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.
[0102] As the lithium metal alloy, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.
[0103] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. Examples of the Si-based negative electrode active material include silicon, silicon-carbon composite, and SiO x(0 < x < 2), Si-Q alloy (where Q is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Si), examples of the Sn-based negative electrode active material include Sn, SnO2, Sn-R alloy (where R is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Sn), etc., and at least one of these can also be used in combination with SiO2. As the elements Q and R, those selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof can be used.
[0104] The silicon-carbon composite may be a silicon-carbon composite including, for example, a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon precursor may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resin such as phenol resin, furan resin, or polyimide resin. At this time, the content of silicon may be 10% by weight to 50% by weight based on the total weight of the silicon-carbon composite. The content of the crystalline carbon may be 10% by weight to 70% by weight based on the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20% by weight to 40% by weight based on the total weight of the silicon-carbon composite. The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D50) of the silicon particles may be 10 nm to 200 nm. The silicon particles may be present in an oxidized form, and the ratio of the atomic content of Si:O in the silicon particles, which indicates the degree of oxidation, may be 99:1 to 33:67. x particles, in which case SiO x Here, x may range from more than 0 to less than 2. Unless otherwise defined herein, the average particle size (D50) refers to the diameter of particles whose cumulative volume is 50% by volume in the particle size distribution.
[0105] The Si-based or Sn-based negative electrode active material may be mixed with a carbon-based negative electrode active material, and the weight ratio of the Si-based or Sn-based negative electrode active material to the carbon-based negative electrode active material may be 1:99 to 90:10.
[0106] The content of the negative active material in the negative active material layer may be 95 wt % to 99 wt % based on the total weight of the negative active material layer.
[0107] In one embodiment, the negative electrode active material layer may further include a binder and may optionally further include a conductive material. The content of the binder in the negative electrode active material layer may be 1 wt% to 5 wt% based on the total weight of the negative electrode active material layer. When the conductive material is further included, the negative electrode active material layer may include 90 wt% to 98 wt% of the negative electrode active material, 1 wt% to 5 wt% of the binder, and 1 wt% to 5 wt% of the conductive material.
[0108] The binder serves to effectively adhere the negative active material particles to each other and to the current collector. The binder may be a water-insoluble binder, a water-soluble binder, or a combination thereof.
[0109] Examples of the non-water-soluble binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.
[0110] The water-soluble binder may be a rubber-based binder or a polymeric resin binder. The rubber-based binder may be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymeric resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0111] When a water-soluble binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used. The content of such a thickener may be 0.1 to 3 parts by weight per 100 parts by weight of the negative electrode active material.
[0112] The conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof.
[0113] The negative electrode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0114] Lithium secondary battery Another embodiment provides a lithium secondary battery including a positive electrode, a negative electrode, a separator positioned between the positive electrode and the negative electrode, and an electrolyte.
[0115] 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG 1, a lithium secondary battery 100 according to an embodiment includes a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 disposed between the positive electrode 114 and the negative electrode 112, and a lithium secondary battery electrolyte impregnated in the positive electrode 114, the negative electrode 112, and the separator 113, a battery container 120 including the battery cell, and a sealing member 140 sealing the battery container 120.
[0116] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0117] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. As the non-aqueous organic solvent, carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents can be used. As the carbonate-based solvent, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and examples of the ketone solvent include cyclohexanone, etc. The alcohol solvent may be ethyl alcohol, isopropyl alcohol, or the like, and the aprotic solvent may be nitriles such as R-CN (wherein R is a C2-C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond, an aromatic ring, or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, sulfolanes, or the like.
[0118] The non-aqueous organic solvent may be used alone or in combination of two or more thereof. When two or more thereof are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those skilled in the art.
[0119] In addition, in the case of the carbonate-based solvent, a cyclic carbonate and a chain carbonate can be mixed and used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.
[0120] The non-aqueous organic solvent may further include an aromatic hydrocarbon-based organic solvent in addition to the carbonate-based solvent, and the carbonate-based solvent and the aromatic hydrocarbon-based organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.
[0121] The aromatic hydrocarbon solvent may be an aromatic hydrocarbon compound represented by the following formula I:
[0122] [ka]
[0123] In the above formula I, R 4 ~R 9 are the same or different and are selected from the group consisting of hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, a haloalkyl group having 1 to 10 carbon atoms, and combinations thereof.
[0124] Specific examples of the aromatic hydrocarbon solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorobenzene ... and combinations thereof.
[0125] The electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following formula II as a life-improving additive in order to improve the battery life.
[0126] [ka]
[0127] In the above formula II, R 10 and R 11 are the same or different and are selected from the group consisting of hydrogen, a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, 10 and R 11At least one of R is selected from the group consisting of a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, with the proviso that 10 and R 11 is not hydrogen at the same time.
[0128] Representative examples of the ethylene carbonate-based compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When such a life-improving additive is further used, the amount of the additive used can be appropriately adjusted.
[0129] The lithium salt is a material that is dissolved in a non-aqueous organic solvent and acts as a source of lithium ions in a battery to enable basic operation of a lithium secondary battery and to promote the movement of lithium ions between a positive electrode and a negative electrode.
[0130] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1and lithium difluoro(bisoxalato)borate (LiDFOB).
[0131] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively migrate lithium ions.
[0132] The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a path for lithium ions to move, and can be any material that is generally used in lithium ion batteries. In other words, a material that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability can be used. For example, the separator can be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and can be in the form of a non-woven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials to ensure heat resistance or mechanical strength can also be used, and can be selectively used in a single-layer or multi-layer structure.
[0133] Lithium secondary batteries can be classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, into cylindrical, square, coin, pouch, etc. types depending on the shape, and into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in the art, so a detailed description will be omitted.
[0134] The lithium secondary battery according to an embodiment has a high capacity and is excellent in storage stability at high temperatures, life characteristics, and high rate characteristics, and can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices.
[0135] Examples of the present invention and comparative examples are described below. The following examples are merely examples of the present invention, and the present invention is not limited to the following examples.
[0136] Example 1 1. Preparation of primary nickel-based oxide in the form of secondary particles [Co-precipitation process] The metal raw materials, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O), were dissolved in distilled water as a solvent in a molar ratio of 95:4:1 to prepare a mixed solution, and ammonia water (NH4OH) and sodium hydroxide (NaOH) were prepared as a precipitant to form a complex compound.
[0137] After feeding the ammonia water dilution solution into the continuous reactor, the metal raw material mixed solution is continuously fed, and sodium hydroxide is fed to maintain the pH inside the reactor. The reaction is carried out slowly for about 80 hours, and when the reaction is stabilized, the overflowing product is collected and washed and dried to obtain the final precursor. As a result, the primary particles are aggregated to produce the first nickel-based hydroxide (Ni 0.95Co 0.04 Mn 0.01 (OH)2) is obtained, washed and dried.
[0138] [Oxidation process] The first nickel hydroxide (Ni 0.95 Co 0.04 Mn 0.01 (OH)2) was mixed with LiOH so that the mole ratio of lithium to the total amount of transition metals was 1.04, and the mixture was subjected to a first heat treatment at about 750°C for 15 hours in an oxygen atmosphere to obtain a first nickel-based oxide (LiNi 0.95 Co 0.04 Mn 0.01 O2) is obtained. The average particle size of the obtained first nickel-based oxide is about 15 μm, and the primary particles are aggregated to form secondary particles.
[0139] 2. Preparation of second nickel-based oxide in single particle form [Co-precipitation process] A mixed solution is prepared by dissolving nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O) in distilled water as a solvent. A diluted ammonia water (NH4OH) solution and sodium hydroxide (NaOH) as a precipitant are prepared to form a complex compound. After that, the mixed solution of the metal raw materials, ammonia water, and sodium hydroxide are each placed into the reactor. The reaction is then carried out for approximately 20 hours while stirring. The slurry solution in the reactor is then filtered and washed with high-purity distilled water, and then dried for 24 hours to obtain the second nickel hydroxide (Ni 0.94 Co 0.05 Mn 0.01 The resulting second nickel hydroxide powder has an average particle size of about 4.0 μm and a specific surface area measured by the BET measurement method of about 15 m 2 / g.
[0140] [Oxidation process] The obtained second nickel-based hydroxide and LiOH are mixed to satisfy Li / (Ni+Co+Mn)=1.05, and then the mixture is put into a sintering furnace and subjected to a second heat treatment at 910°C for 8 hours in an oxygen atmosphere. The obtained material is then crushed for about 30 minutes to separate / disperse the second nickel-based oxide in the form of single particles. The obtained second nickel-based oxide in the form of single particles (LiNi 0.94 Co 0.05 Mn 0.01 The average particle size of O2) is about 3.7 μm.
[0141] 3. Boron coating and production of final positive electrode active material The first nickel-based oxide and the second nickel-based oxide are mixed in a weight ratio of 7:3, and the weight ratio of this mixture to water is set to 1:1, followed by washing with water in a stirrer and drying at 150°C. 5 moles of lithium hydroxide and 0.25 moles of boric acid (B(OH)3) are added to 100 moles of transition metals excluding lithium in the nickel-based oxide as a whole and then mixed into a sintering furnace, followed by a third heat treatment in an oxygen atmosphere at about 710°C for 15 hours. The sintering furnace is then cooled to room temperature to obtain the final positive electrode active material in which the first positive electrode active material and the second positive electrode active material are mixed.
[0142] The final positive electrode active material is a mixture of the first positive electrode active material in the form of secondary particles and the second positive electrode active material in the form of single particles, each of which is coated with a boron-containing compound.
[0143] 4. Fabrication of the Positive Electrode 95% by weight of the final positive electrode active material, 3% by weight of polyvinylidene fluoride binder, and 2% by weight of carbon nanotube conductive material are mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry is applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.
[0144] 5. Manufacturing of lithium secondary batteries A coin half cell is manufactured by using the prepared positive electrode and lithium metal counter electrode, and injecting an electrolyte solution of 1.0 M LiPF6 lithium salt added to a solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 50:50, via a polyethylene-polypropylene multilayer separator between them.
[0145] Comparative Example 1 A cathode active material and a battery are manufactured in the same manner as in Example 1, except that in "3. Boron coating and manufacturing of final cathode active material", after mixing the first nickel-based oxide and the second nickel-based oxide, boron coating is not performed, but the first nickel-based oxide and the second nickel-based oxide are separately boron-coated and then mixed.
[0146] The boron coating process is as follows. The first nickel-based oxide is mixed with 5 mol parts of lithium hydroxide and 0.25 mol parts of boric acid per 100 mol parts of total elements excluding Li and O, and then placed in a sintering furnace, and then heat-treated at about 700°C for 15 hours in an oxygen atmosphere, and the sintering furnace is cooled at room temperature to obtain a first positive electrode active material. The second nickel-based oxide is mixed with 5 mol parts of lithium hydroxide and 0.25 mol parts of boric acid per 100 mol parts of total elements excluding Li and O, and then heat-treated at about 850°C for 15 hours in an oxygen atmosphere, and the sintering furnace is cooled at room temperature to obtain a second positive electrode active material. The first positive electrode active material coated with the boron-containing compound and the second positive electrode active material coated with the boron-containing compound are mixed in a weight ratio of 7:3 to prepare a final positive electrode active material according to Comparative Example 1.
[0147] Evaluation example 1: Surface observation of positive electrode active material In the final cathode active material prepared according to Example 1, a SEM photograph of the surface of the first cathode active material is shown in FIG. 2, and SEM photographs of the second cathode active material are shown in FIG. 3 and FIG. 4. Referring to FIG. 2, it can be seen that the first cathode active material is in the form of secondary particles in which a large number of primary particles are aggregated, and there is no change in surface roughness after boron coating. Referring to FIG. 3 and FIG. 4, it can be seen that the second cathode active material is in the form of a single particle, and the portion of the single particle surface indicated by a thin circle is the portion coated with a boron-containing compound, where unevenness occurs on the surface and the surface roughness is clearly increased, and the portion indicated by a thick circle is the portion not coated with a boron-containing compound, where the surface is uniform and flat and the surface roughness is not increased.
[0148] In the final cathode active material according to Comparative Example 1, an SEM photograph of the surface of the first cathode active material is shown in FIG 5, and an SEM photograph of the second cathode active material is shown in FIG 6. Referring to FIG 5, it can be seen that the first cathode active material is in the form of secondary particles and there is no particular change in surface roughness. Referring to FIG 6, it can be seen that the second cathode active material is in the form of single particles, and unlike Example 1, the entire surface of the single particle is uniform and flat.
[0149] Evaluation example 2: Evaluation of surface roughness of positive electrode active material The surface roughness of the positive active materials prepared in Example 1 and Comparative Example 1 was measured using a surface roughness tester using an atomic force microscope (DME UHV AFM; scan speed 0.25 μm / s, non-contact mode range 250 nm x 250 nm), and the results are shown in Table 1 below. In Table 1, the unit of each value is nm.
[0150] [Table 1]
[0151] Evaluation example 2: Initial charge / discharge capacity, efficiency, and life characteristics Each of the coin half cells of Example 1 and Comparative Example 1 was charged under constant current (0.2C) and constant voltage (4.25V, 0.05C cut-off) conditions to measure the charge capacity, and then rested for 10 minutes, and discharged to 3.0V under constant current (0.2C) conditions to measure the discharge capacity. The ratio of the discharge capacity to the charge capacity is expressed as efficiency. The results are shown in Table 2 below.
[0152] In addition, after the initial charge and discharge, the battery was charged and discharged 50 times at 45°C and 1C, and the discharge capacity after 50 cycles was measured. The ratio (%) of the 50th discharge capacity to the initial discharge capacity is shown in Table 2 as the capacity retention rate, i.e., the life characteristics.
[0153] [Table 2]
[0154] Referring to Table 2, it can be seen that the battery of Example 1 has improved initial charge capacity, initial discharge capacity, and initial charge / discharge capacity, as well as improved life characteristics, compared to the battery of Comparative Example 1.
[0155] The first and second positive electrode active materials are both coated with a boron-containing compound, but in the case of the second positive electrode active material in single particle form, the boron-containing compound is effectively coated only on some surfaces, resulting in some uneven surfaces and an increase in the specific surface area. It has been confirmed that batteries using this positive electrode active material have improved characteristics such as initial charge / discharge efficiency and lifespan.
[0156] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0157] 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Positive electrode 120:Battery container 140: Sealing member
Claims
1. a first positive electrode active material including a lithium nickel-based composite oxide, the first positive electrode active material including a secondary particle formed by agglomerating a plurality of primary particles and a boron coating portion located on a surface of the secondary particle; A second positive electrode active material includes a lithium nickel-based composite oxide, the second positive electrode active material including a single particle and a boron coating portion located on a surface of the single particle, the second positive electrode active material has an uneven surface having a high surface roughness and a flat surface having a surface roughness lower than that of the uneven surface, the uneven surface of the second positive electrode active material has a maximum roughness (R max ; peak to peak height) of 15 nm or more; the flat surface of the second positive electrode active material has a maximum roughness (R max ; peak to peak height) of 14 nm or less; the uneven surface of the second positive electrode active material is a surface on which the boron coating portion is present, The flat surface of the second positive electrode active material is a surface on which the boron coating portion is not present.
2. the boron coating portion includes a boron-containing compound; 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the boron-containing compound comprises boron oxide, lithium borate, or a combination thereof.
3. The boron-containing compound is B 2 O 2 , B 2 O 3 , B 4 O 3 , B 4 O 5 , LiBO 2 , Li 3 B 7 O 12 , Li 6 B 4 O 9 , Li 3 B 11 O 18 , Li 2 B 4 O 7 , Li 3 B.O. 3 3. The positive electrode active material for a lithium secondary battery according to claim 2, wherein the positive electrode active material is one of the above or a combination thereof.
4. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the content of boron in the positive electrode active material for lithium secondary batteries is 0.01% by weight to 3% by weight based on the total content of elements excluding lithium and oxygen.
5. The uneven surface of the second positive electrode active material has an average roughness (R a ; average roughness) is 1.2 nm or more, and the root mean square roughness (R q 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the mean square roughness (mean square roughness; root mean square roughness) is 1.5 nm or more.
6. The flat surface of the second positive electrode active material has an average roughness (R a ) is less than 1.2 nm, and the root mean square roughness (R q 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle diameter is less than 1.5 nm.
7. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the ratio of the uneven surface to the total surface area of the second positive electrode active material is 40% to 80%.
8. The BET specific surface area of the positive electrode active material for a lithium secondary battery including the first positive electrode active material and the second positive electrode active material is 0.2 m 2 / g to 0.6 m 2 The positive electrode active material for a lithium secondary battery according to claim 1, wherein the Mo content is 1 / g.
9. The average particle size of the first positive electrode active material is 5 μm to 25 μm, 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the second positive electrode active material is 1 μm to 8 μm.
10. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material is contained in an amount of 50% by weight to 90% by weight, and the second positive electrode active material is contained in an amount of 10% by weight to 50% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material.
11. The first positive electrode active material includes a lithium nickel-based composite oxide represented by the following chemical formula 1: The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the second positive electrode active material comprises a lithium nickel-based composite oxide represented by the following chemical formula 11: [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 (wherein, in the formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, 0≦y1≦0.7, 0≦z1≦0.7, 0.9≦x1+y1+z1≦1.1, and 0≦b1≦0.1; M 1 and M. 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S. [Chemical formula 11] Li a11 Ni x11 M 11 y11 M 12 z11 O 2-b11 X b11 (In the above formula 11, 0.9≦a11≦1.8, 0.3≦x11≦1, 0≦y11≦0.7, 0≦z11≦0.7, 0.9≦x11+y11+z11≦1.1, and 0≦b11≦0.1; M 11 and M. 12 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.
12. A first nickel-based hydroxide and a lithium source are mixed and subjected to a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles formed by agglomeration of a plurality of primary particles; Mixing the second nickel-based hydroxide and the lithium raw material and subjecting them to a second heat treatment to prepare a second nickel-based oxide in the form of a single particle; and A method for producing a positive electrode active material for a lithium secondary battery, comprising mixing a first nickel-based oxide, a second nickel-based oxide, and a boron raw material, and subjecting the mixture to a third heat treatment.
13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the first nickel hydroxide and the second nickel hydroxide are each independently represented by the following chemical formula 21: [Chemical formula 21] Ni x21 M 21 y21 M 22 z21 (OH) 2 (In the above formula 21, 0.3≦x21≦1, 0≦y21≦0.7, 0≦z21≦0.7, and 0.9≦x21+y21+z21≦1.1; M 21 and M. 22 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
14. Mixing the first nickel-based hydroxide and the lithium raw material means mixing so that the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide is 0.9 or more and 1.2 or less, 13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the second nickel-based hydroxide and the lithium raw material are mixed so that the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide is 0.9 or more and 1.2 or less.
15. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the first heat treatment is carried out at a temperature in the range of 600° C. to 900° C. for 5 hours to 20 hours.
16. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein preparing the second nickel-based oxide comprises performing a second heat treatment at 800° C. to 1100° C. for 5 hours to 20 hours and pulverizing the second nickel-based oxide.
17. 13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the first nickel-based oxide and the second nickel-based oxide are mixed so that a weight ratio of the first nickel-based oxide to the second nickel-based oxide is 9:1 to 5:
5.
18. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the first nickel-based oxide, the second nickel-based oxide, and the boron raw material are mixed such that the amount of boron contained in the boron raw material is 0.01 to 3 parts by mol when the total content of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide is 100 parts by mol.
19. The method for producing a positive electrode active material for a lithium secondary battery according to claim 12, wherein the third heat treatment is carried out at a temperature in the range of 650° C. to 900° C. for 5 hours to 30 hours.
20. A lithium secondary battery comprising a positive electrode containing the positive electrode active material for lithium secondary batteries according to any one of claims 1 to 11, a negative electrode, and an electrolyte.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, manufacturing method for the same, and lithium secondary battery including positive electrode including the same
JP2022082508A
Positive-electrode active material for non-aqueous-electrolyte secondary cell and method for manufacturing said positive-electrode active material, positive-electrode mixture paste for non-aqueous-electrolyte secondary cell, and non-aqueous-electrolyte secondary cell
WO2019039567A1